Společné stanovisko českých odborných společností ke konsenzu European Atherosclerosis Society a European Federation of Clinical Chemistry and Laboratory Medicine k vyšetřování krevních lipidů a k interpretaci jejich hodnot - Soška, Vladimír; Franeková, Janka; Friedecký, Bedřich; Jabor, Antonín; Kraml, Pavel; Rosolová, Hana; Vrablík, Michal (Vnitrni lekarstvi, 2016)
The aim of this opinion is to summarize and to comment the consensus of the European Atherosclerosis Society and European Federation of Clinical Chemistry and Laboratory Medicine, which covers two main areas: 1) whether it is necessary / required to be fasting or non-fasting before blood sampling for lipids measurement, and what are the changes in the concentration of blood lipids during the day; 2) What decision limits (cut off value) of lipids and lipoproteins should be reported from laboratories and what is the recommended procedure for people with extreme / critical blood lipid values. Following parameters are discused: total cholesterol, LDL cholesterol, HDL cholesterol, non-HDL cholesterol, triglycerides, apolipoprotein A1, apolipoprotein B, lipoprotein(a). This opinion should be the object of interest both for professionals in clinical laboratories and for physicians in hospitals and out-patients departments.Key words: apolipoproteins - blood collection - cholesterol - laboratory testing - lipoprotein(a) - cut off limits - triglycerides.
Keywords: Cholesterol; Triglycerides; Cholesterol, HDL; Cholesterol, LDL; Consensus; Humans; cholesterol; Chemistry, Clinical; Lipoproteins; Female; klinické laboratorní techniky; ateroskleróza; lidé; společnosti lékařské; LDL-cholesterol; klinická chemie; konsensus; Apolipoproteins; triglyceridy; apolipoproteiny; ženské pohlaví; Male; Atherosclerosis; HDL-cholesterol; Czech Republic; Clinical Laboratory Techniques; Societies, Medical; lipoproteiny; Česká republika; mužské pohlaví